PENGARUH PELATIHAN SISTEM APLIKASI PRODUK DAN DISIPLIN TERHADAP KINERJA KARYAWAN WAREHOUSE PADA PT.SCHNEIDER ELECTRIC MANUFACTURING BATAM - Mirwan M; Dhenny Asmarazisa; Tibrani Tibrani (BENING, 2017)
The research aims to examine and analyze the Product application system training and work discipline toward performance of employee at warehouse in PT Schneider Electric Manufacturing Batam. Data collected through distribution of questionnaires and it is implemented to at warehouse in PT Schneider Electric Manufacturing Batam’s 41 employee. Analysis of data in this research using the help of SPSS A sampling technique uses a census method and data test technique is used within the research includes validity test by factor analysis, reliability test with cronbach. Classic assumption test and double linear regression analysis, to verify and to prove the research hypothesis.Analysis result demonstrates that leadership style have a positive influence toward employee performance. Motivation have a positive influence toward employee performance and work discipline have a positive influence toward employee performance.